The autecology of Azolla filiculoides Lamarck with special reference to its occurrence in the Hendrik Verwoerd Dam catchment area - Ashton, Peter John (Rhodes University, Faculty of Science, Botany Department, 1983)
An autecological study of the heterosporous fern Azolla filiculoides Lamarck and its endosymbiotic blue-green alga Anabaena azollae Strasburger, based on a combination of field and laboratory studies, is presented. The taxonomy, morphology and anatomy of the fern-alga association were studied as well as nutritional and physiological aspects of the symbiosis. These studies have defined the habitat and nutritional requirements of the fern and have provided new insights into its reproductive biology, nitrogen metabolism and the nature of the association between the fern and alga. In the catchment area of the Hendrik Verwoerd Dam the availability of suitably sheltered habitat limits the distribution of A. filiculoides while the availability of nutrients, in particular calcium, phosphorus and iron, limits the growth of the fern. The multilayered mats formed by A. filiculoides are essential for spore production, cause dramatic changes in the hydrochemistry of the underlying waters and confer a great competitive advantage on the plant. Methods for the isolation of the fern and algal components of the symbiosis have been developed but recombination of the individual organisms to reform the symbiosis was unsuccessful. The development of the fern is closely linked to that of the alga and the association is maintained throughout the life cycle of the fern. Because of its specific habitat and nutritional requirements, A. filiculoides is unlikely to colonize the open waters of the Hendrik Verwoerd Dam.
Keywords: Azolla filiculoides -- South Africa -- Gariep Dam; Azollaceae Azolla -- South Africa -- Gariep Dam; Water ferns -- South Africa -- Gariep Dam; Aquatic weeds -- South Africa